Islamism, the West and Our Concern: A Social Reflection - TI Aisyah; Herdi Sahrasad; Muhammad Ridwan; Muhamad Asrori Mulky; Dedy Tabrani; Al Chaidar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This article argues that a number of Western orientalists tried to impress that Islam and the West could not meet, imaged that all the Islamic ones seemed to be unable to meet all the nuances of the West, as all the western images imaged always contradict Islam. Such tensions continue to this day. Towards the end of the 20th century, Islamism or Islamic fundamentalism has retreated or failed in maintaining political power in the Islamic world. But the enforcement of Shari'ah in society, remains a central theme of the demands of these Islamic fundamentalists. Thus, their target as a group is no longer just a country, but also a society. The political experiments of Islam, however, as shown in Algeria, Sudan, Iran and Afghanistan have failed and are out of date, but anyway, by the beginning of the 21st century Islamism or Islamic fundamentalism has been revived, marked by the WTC bomb 9/11 and other terror attacks in Indonesia, Europe, the US etc.